(untitled) (Orinoquia, 2014)
The production of the Amazonian fish Cachama blanca has been rising continuously and its cultivation has become heavily dependent on the provision of supplementary feed at low cost. Information on the suitability of locally available, cheap feed sources for this fish is required. The locally available duckweeds (Lemna minor and Spirodela polyrhiza) and water fern (Azolla filiculoides) were tested in Cachama blanca evaluating growth performance, feed conversion ratio, and digestibility. A total of five diets, four test diets (35% crude protein) supplemented with fermented duckweeds (DW) and water fern (WF) at 15% and 25% inclusion level and a control diet without aquatic plants, were compared. Ingredients were processed in a micro extruder. Diets were based on a low-fish meal diet. A total of 390 fish (1.6 ± 0.02 g) were randomly selected and stocked into fifteen 250 L plastic tanks providing three replicates per diet. Tanks were arranged in a recirculating system comprising a biofilter and aeration with a turn-over of and a daily water exchange. Fish were fed to apparent satiation twice a day for 60 days. Fish from each tank were weighed collectively every 2 weeks to monitor growth and after 8 weeks final biomass of each tank was recorded. Data from each treatment were subjected to one-way analysis of variance (ANOVA) of the triplicate groups (n=3). Fish fed on DW15 and WF15 revealed significantly higher (P<0.05) SGR and weight gain than fish fed the other diets. Feed intake did not vary among diets (P>0.05). FCR and PER were also better (P<0.05) for fish fed on DW15 and WF15 than for fish fed on DW25 and WF25 but not significant compared to the control diet. Apparent digestibility coefficients decreased significantly (P<0.05) in DW25 and WF25 diets. Fish feed supplementation with the fermented aquatic macrophytes at 15% inclusion level improved the growth performance of Cachama blanca (P. brachypomus) fed on low-fishmeal-diets.